COVID-19 in Patients With Hematologic Malignancies: A Single Center Retrospective Study - Wang, Xuejun Alice; Binder, Adam F.; Gergis, Usama; Wilde, Lindsay (Frontiers in Oncology, 2021)
Initial studies that described the novel coronavirus (COVID-19) reported increased morbidity and mortality in patients with cancer. Of this group, patients with hematologic malignancies (HM) had the highest disease severity and death rates. Subsequent studies have attempted to better describe how COVID-19 affects patients with HM. However, these studies have yielded variable and often contradictory results. We present our single-institution experience with patients with HM who were diagnosed with COVID-19 from March 2020 to March 2021. We report 62 total cases with 10 patients who died during this time (mortality rate of 16.1%). The median age of patients was 67 years (range 20-89 years). 55% of patients had lymphoid malignancies and the majority had active disease at the time of diagnosis with COVID-19. 87% of patients had more than 1 co-morbidity. Important co-morbidities included cardiovascular disease and smoking history. 38.7% of patients had asymptomatic or mild disease, 54.8% required hospitalization, and 17.5% required ICU level care. In patients who required ICU level care, the mortality was 60%.